Atomização a gás da liga de alumínio AA2017: efeitos dos parâmetros de processo nas características físicas dos pós produzidos visando aplicação em manufatura aditiva - Pinotti, Vitor Eduardo (2022)
Gas atomization is the main method to produce metal powders for LASER powder bed fusion (L-PBF), which is an additive manufacturing (AM) technique. It produces metallic powders with suitable characteristics to be applied in AM/L-PBF. The optimization of the parameters involved in the gas atomization process is necessary to produce powders with good fluidity and high apparent density, which are preconditions to be used in the L-PBF. The choice of an optimal set of parameters can also provide an increase in powder production yield. However, the optimization of this process is complex, because there are many parameters involved and, therefore, a systematic study must be carried out to better understand their correlation with the powder’s characteristics and their application (e.g. MA/L-PBF, for that research). Based on this context, this work aimed to study the influence of the three main process parameters at two levels (nozzle diameter (0): 1.5-2.5 mm; superheating temperature (Δ): 75-150 ºC; atomization pressure (): 20-40 Bar) on the physical characteristics of AA2017 aluminum alloy powders. It was identified that the average particle size (50) was poorly affected by the variation of parameters, while the width of the particle size distribution curve was significantly altered. The more suitable powder to be applied in AM/L-PBF was produced in an experiment with a specific set of parameters (0=1.5mm; Δ =150 ºC; = 20 Bar). It presents appropriate fluidity (funnel of Carney) and suitable apparent density: 0.28 s/g and 1.51 ± 0.02 g/cm3, respectively. These behaviors occurred due to an optimal combination of granulometric distribution and morphology. Finally, mathematical analysis was performed, in which the results obtained experimentally were compared with theoretical calculations based on the Lubanska equation. A good correlation was observed between the measured and calculated mean particle size (R2 = 0.97).